Algorithmic Information Theory, Third Printing - Chaitin, G J (Cambridge University Press, 2012)
Chaitin, the inventor of algorithmic information theory, presents in this book the strongest possible version of Gödel's incompleteness theorem, using an information theoretic approach based on the size of computer programs